The Social Belongingness as the Need to the Interpersonal Feelings in the Novel Fangirl by Rainbow Rowell - Anisa Zakinah Burhan; Sumardjo Sumardjo; Adi Prautomo (Faculty of Letters Universitas Balikpapan, 2019)
This study aims to find the social belongingness as the need to the interpersonal feelings. There are two objectives in this research 1) to find out the social belongingness happen in the society 2) to describe how the social belonging as the need effect the interpersonal feelings in the novel Fangirl by Rainbow Rowell. This research is based on Psychology of Humanistic theory by Abraham Maslow’s theory of hierarchy of needs. Based on the result of this research, the researcher found the emerge of social belongingness need effecting the interpersonal feelings in the novel Fangirl by Rainbow Rowell.